Blast retrofit of one-way reinforced concrete members using externally bonded FRP and FRP anchorage. Issue 2 (June 2022) - Jackson, Christopher M.; Jacques, Eric; Saatcioglu, Murat
This paper presents the results of nine as-built and carbon fiber reinforced polymer (CFRP) retrofitted reinforced concrete panels subjected to simulated blast loading using a pneumatically operated shock tube. The objective of the study was to characterize the blast response of CFRP retrofitted reinforced concrete panels, with and without supplemental mechanical anchorage applied to the CFRP. The results indicate that retrofitting can significantly increase the strength and stiffness of reinforced concrete flexure members and greatly enhance the displacement time-history response over non-retrofitted members. Debonding of the externally bonded CFRP was the failure mode for all retrofitted members. FRP anchors, designed to prevent or delay debonding failures through mechanical end-anchorage, were found to substantially enhance the performance of panels experiencing critical diagonal crack debonding. However, the FRP anchors were found to have no substantial effect on retrofit performance for the case plate-end interfacial debonding failures. In addition, the displacement time-histories for as-built and FRP retrofitted panel obtained through detail single degree of freedom analysis were found correlate well with those obtained experimentally. Finally, a discussion on the practical considerations of using externally bonded FRP retrofits to resist blast loads and recommendations for protective design are presented.